Scanning program of image guided missile basing on parabolic trajectory - Wang Yandong (2011 3rd International Conference on Advanced Computer Control, 2011)
In order to have a larger scanning area of image guided missile which fight baseing on parabolic trajectory, improve the probability of capture by the seeker, a program is presented in the paper. The program not only can meet the requirement of the capture probability, but also can scan the whole area of target maneuvering, and there is no blind area in the scanning area.